Sexual networks, sexual practices, and sexual health among youths in WHO-South East Asia Region: a scoping review protocol - Amrita Rao; Rashmi Shinde; Sheikh Mohammed Shahabuddin (Systematic Reviews)
Abstract Background South-East Asia Region has one of the largest youth populations in the world. All countries are striving to achieve the sustainable development goal by 2030; hence, it is important to prioritize healthcare services for youths. Youths in the age bracket of 18 to 24 years often engage in high-risk behaviors such as unsafe injecting practices/substance abuse. These high-risk practices lead to increased transmission of sexually transmitted infections including HIV among them. It is imperative to understand the dynamics around sexual transmission of diseases among youth. This review will map the available evidence and identify the gaps in sexual health interventions related to the sexual networks, sexual practices, and sexual health among youths across the World Health Organization (WHO)-South East Asia Region (SEAR). Methods The scoping review is guided by the Arksey and Malley framework. Peer-reviewed articles focusing on youths in the age groups of 18 to 24 years, from the 11 countries of SEAR, will be accessed from three databases, namely PubMed, Scopus, and Journals@Ovid. Additionally, grey literature from 2015 to date will also be accessed. Two reviewers will independently screen the articles based on pre-defined eligibility criteria in Rayyan software. Data extraction will be carried out based on pre-specified variables aligned with the objectives. We will synthesize the evidence from the relevant qualitative, quantitative, and mixed method studies. The reporting will follow Preferred Reporting Items for Systematic reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR). Discussion This review will help to generate evidence focusing on the current sexual networks, sexual practices, and sexual health among youths in WHO SEAR with a focus on India, highlighting the gaps in sexual health interventions that need to be bridged. The insights from this review will assist in designing larger evidence-based intervention studies for improving the sexual networks, sexual practices, and sexual health among youths in this region. The findings from this review will be disseminated through peer-reviewed journals and conferences. Systematic review registration Open Science Framework. The link is https://doi.org/10.17605/OSF.IO/2JSMC .